BOWEL CONTROL FUNCTION OF PATIENTS AFTER ANAL SPHINCTER RUPTURE SURGERY AT VIET DUC UNIVERSITY HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
The objective of this study was to evaluate the bowel control function of patients after anal sphincter rupture surgery using the Wexner scale in 2025. A cross-sectional descriptive study was conducted on 18 inpatients treated at the Department of Colorectal and Perineal Surgery from January to December 2025. The results showed that females accounted for the majority (83.33%), with an average age of 32.55 ± 11.29. The majority of surgical causes were obstetric (55.56%), and trauma (44.44%). The study showed that the mean Wexner score for fecal incontinence decreased from 1.72 ± 1.56 at 7 days post-surgery to 0.17 ± 0.51 at 1 month post-surgery with p < 0.001, which was statistically significant. The Wexner scale is a useful system for determining the severity of fecal incontinence. Healthcare professionals should be encouraged to use the Wexner scale to monitor patients clinically.
Keywords: Bowel control function; anal sphincter rupture surgery; Viet Duc University Hospital.